Effects of Canonical NF-κB Signaling Pathway on the Proliferation and Odonto/Osteogenic Differentiation of Human Stem Cells from Apical Papilla. (23rd April 2014) - Li, Junjun; Yan, Ming; Wang, Zilu; Jing, Shuanglin; Li, Yao; Liu, Genxia; Yu, Jinhua; Fan, Zhipeng
Abstract : Background Information . NF- κ B signaling pathway plays a complicated role in the biological functions of mesenchymal stem cells. However, the effects of NF- κ B pathway on the odonto/osteogenic differentiation of stem cells from apical papilla (SCAPs) remain unclear. The present study was designed to evaluate the effects of canonical NF- κ B pathway on the osteo/odontogenic capacity of SCAPs in vitro . Results . Western blot results demonstrated that NF- κ B pathway in SCAPs was successfully activated by TNF- α or blocked by BMS-345541. NF- κ B pathway-activated SCAPs presented a higher proliferation activity compared with control groups, as indicated by dimethyl-thiazol-diphenyl tetrazolium bromide assay (MTT) and flow cytometry assay (FCM). Wound scratch assay revealed that NF- κ B pathway-activated SCAPs presented an improved migration capacity, enhanced alkaline phosphatase (ALP) activity, and upregulated mineralization capacity of SCAPs, as compared with control groups. Meanwhile, the odonto/osteogenic markers ( ALP /ALP, RUNX2 /RUNX2, OSX /OSX, OCN /OCN, OPN /OPN, BSP /BSP, DSPP /DSP, and DMP-1 /DMP-1) in NF- κ B pathway-activated SCAPs were also significantly upregulated as compared with control groups at both protein and mRNA levels. However, NF- κ B pathway-inhibited SCAPs exhibited a lower proliferation/migration capacity, and decreased odonto/osteogenic ability in comparison with control groups. Conclusion . Our findings suggest that classical NF- κ B pathway plays a paramount role in the proliferation and committed differentiation of SCAPs.